WORMY OF THE TRANSMISSION ENERGETIC AND POWER CHARACTERISTICS - RO'. Siddikov; O. M. Khoshimov (Journals Park Publishing, 2025)
This in the article wormy transfers types, in them friction and of the transmission energetic and power characteristics according to information illuminated passed. Also, wormy of transmissions application sectors structure , types also information about giving passed.
Keywords: Wormy transmission, energy efficiency, power torque, friction.